PENTINGNYA PEMANFAATAN DATA KEPENDUDUKAN DI ERA DIGITAL - Sri Handriana Dewi Hastuti (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2020)
Government Work Units to use a one data policy approach. The purpose of using this data includes the use of data for schools, taking care of data licensing, managing social assistance, all of which must be the same as the data sources in the Population and Civil Registration Office so that no more people have different identities. Based on the Minister of Home Affairs Regulation No. 61 of 2015 concerning Requirements, Scope and Procedures for Granting Access Rights and Utilization of Population Identification Number, Population Data, and Electronic Resident Identity Cards, data utilization access permits are granted by the Regent / Mayor. After submitting the permit to the Regent / Mayor, then the Cooperation Agreement (PKS) is signed. Furthermore, the Regional Apparatus Organization or public service agencies form a Technical Team implementing the cooperation. Furthermore, data access will be given according to their needs and usage. The user access institution will be monitored by the Regent / Mayor through the Department of population and civil registration, and periodic control, supervision and evaluation will be conducted.